Cultural Translation and Mamoni Raisom Goswami’s Thang Fhâkhri Tahcildârar Tâmar Tarowâl - Purabi Goswami (Transcript: An e-Journal of Literary and Cultural Studies, 2021)
The act of translation cannot be called a simple act of conveyance because a text is a product of a cultural milieu. Hence when a text is translated it does not remain a plain act of transfer from one language to another, it becomes an act of cultural transference. The paper dwells on this aspect of translation and analyses my own experience of translating Mamoni Raisom Goswami’s Thang Fhâkhri Tahcildârar Tâmar Tarowâl.